2010
DOI: 10.1021/ct100025j
|View full text |Cite
|
Sign up to set email alerts
|

Free Energies of Solvation with Surface, Volume, and Local Electrostatic Effects and Atomic Surface Tensions to Represent the First Solvation Shell

Abstract: Building on the SVPE (surface and volume polarization for electrostatics) model for electrostatic contributions to the free energy of solvation with explicit consideration of both surface and volume polarization effects, on the SMx approach to including first-solvation-shell contributions, and on the linear relationship between the electric field and short-range electrostatic contributions found by Chipman, we have developed a new method for computing absolute aqueous solvation free energies by combining the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 79 publications
3
84
0
Order By: Relevance
“…Such inconsistencies render many continuum model implementations sensitive to cavity size. 37,38 This hypothesis is in the spirit of newly developed charge-dependent radii models 39,40 and foundations of the model for electrostatic contributions to the free energy of solvation with explicit consideration of both surface and volume polarization effects (SVPE) 38 and other adaptive models. 41,42 Therefore, we have screened all possible models and radii combinations to find some composite solvation models that will be able to predict accurately the difference in Gibbs free solvation energies of neutral and reduced forms.…”
Section: Gibbs Solvation Free Energymentioning
confidence: 99%
“…Such inconsistencies render many continuum model implementations sensitive to cavity size. 37,38 This hypothesis is in the spirit of newly developed charge-dependent radii models 39,40 and foundations of the model for electrostatic contributions to the free energy of solvation with explicit consideration of both surface and volume polarization effects (SVPE) 38 and other adaptive models. 41,42 Therefore, we have screened all possible models and radii combinations to find some composite solvation models that will be able to predict accurately the difference in Gibbs free solvation energies of neutral and reduced forms.…”
Section: Gibbs Solvation Free Energymentioning
confidence: 99%
“…For example, the COSMO-RS model 56,57 has been tested for proton exchange and recombination reactions with reasonable accuracy. 58 Other promising approaches are the SMVLE 59 and CMIRS [60][61][62] methods. Essentially, these methods include a term to describe the effect of extremum electric field generated by charged solutes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated reasonable accuracy and excellent agreement with experimentation in many cases. 36,37 ■ ASSOCIATED CONTENT * S Supporting Information Additional information regarding simulation parameters and results are contained in Supplemental Tables 1−7. Table S1 contains standard free energy changes and equilibrium constants of reactions for each of the three TCA cycles.…”
Section: ■ Conclusionmentioning
confidence: 99%